Anti-adhesion ultra-light release material and preparation method thereof

By applying anti-adhesive AB coating and silicone oil layer on the substrate, the problems of insufficient release force and poor appearance of the existing release film are solved, and the effect of ultra-light release force and high flatness is achieved, which is suitable for bonding applications of high flatness screens.

CN115181511BActive Publication Date: 2025-03-14CROWN TAICANG ADHESIVE PROD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210663105.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-13
Publication Date
2025-03-14
Estimated Expiration
2042-06-13

AI Technical Summary

Technical Problem

The existing release films lack release force during peeling, resulting in lower viscosity and poor appearance, especially in bonding occasions with high flatness screens.

Method used

Ultralight release material with anti-adhesion type is prepared by applying an anti-adhesion type AB coating on the back of the substrate and curing it by UV, followed by a silicone oil layer on the other side of the substrate and heat curing it.

Benefits of technology

It realizes ultra-light and stable release force, avoids adsorption and scratching problems, ensures the flatness and cleanliness of the surface, and is suitable for bonding and adhesion of optical adhesive materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115181511B_ABST
    Figure CN115181511B_ABST
Patent Text Reader

Abstract

The present invention relates to an anti-adhesion ultra-light release material and a preparation method thereof. The anti-adhesion ultra-light release material comprises an anti-adhesion AB layer, a release agent coating, and a substrate layer disposed between the anti-adhesion AB layer and the release agent coating. The release layer of the anti-adhesion release material of the present invention adds micron-sized microspheres to the silicone, which can prevent the problem of adhesion adsorption and difficulty in peeling after multi-layer stacking, and also has a certain anti-scratch effect to avoid local poor release.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of release materials, and in particular relates to an anti-adhesion ultra-light release material and a preparation method thereof. Background Art

[0002] Release film, also known as peeling film, isolation film, separation film, adhesive barrier film, thinner paper, release paper, etc., refers to a film that has separation properties after contacting with specific materials under limited conditions. At present, release films with polyester and polyolefin films as base films and coated with silicone materials such as silicone oil or silicone grease on the surface have been used in electronic components, optical components, adhesive products, die-cutting and punching processing industries. According to the different required release force of the release film, the viscosity of the isolation product glue is different, and the release force is adjusted accordingly to achieve an extremely light and stable release force when peeling. The processing of electronic components is becoming more and more refined. Various components are produced by different manufacturers. Assembly manufacturers purchase various components and then assemble them into electronic products. After the production of electronic components is completed, release film is generally used for protection to avoid pollution and damage such as dust during storage and transportation. With the popularization of automation technology, downstream manufacturers basically use automated equipment such as robots for production. The release film on the components of electronic products needs to be peeled off before assembly. The peeling of release film is also increasingly tending to be automatically adsorbed and peeled off by machines. This places more stringent requirements on the release force of the release film. In order to achieve a light enough release force of the release film, the commonly used technical solutions are to increase the amount of silicon coating (CN106221595A) or use surface grid treatment to reduce the contact surface (CN23277224A). These technical solutions can indeed achieve a certain light release force, but increasing the amount of silicon coating too thick will bring about curing difficulties and thus affect the residual adhesion rate. The low residual adhesion rate will have a decreasing effect on the viscosity of the contacting tape. At the same time, too thick silicon coating will make the release surface have a certain adsorption, and many bubbles will appear after the product is rolled up, affecting the appearance; the use of surface grid treatment will cause the adhesive surface to be uneven, thus affecting the appearance, and is not suitable for use in some high-flatness screen bonding occasions, such as OCA glue bonding. Summary of the invention

[0003] In order to solve the above technical problems, in order to achieve a sufficiently light release force of the release film, and at the same time solve the problem of appearance affected by excessive silicon coating or surface gridding treatment, the present invention provides a release material with ultra-light release force and anti-adhesion, which is prepared by first coating a layer of anti-adhesion AB coating on the back of the substrate, after UV curing, and then coating a layer of silicone oil on the other side of the substrate, and after thermal curing.

[0004] The first object of the present invention is to provide an ultra-light release material with anti-adhesion, comprising an anti-adhesion AB layer, a release agent coating and a substrate layer arranged between the anti-adhesion AB layer and the release agent coating, characterized in that, in terms of mass percentage: the ultra-light release material refers to a release force of <5g.

[0005] The anti-adhesion AB layer includes 20%-30% oligomer, 5%-15% diluent monomer, nano-microspheres 1 5%-10%, nano-microspheres 2 3%-5%, photoinitiator 3%-5%, leveling agent 1%-2%, organic solvent 50%-60%;

[0006] The release agent coating comprises 35%-45% of an organic silicon main agent, 1%-5% of a bridging agent, 1%-3% of an anchoring agent, 40%-60% of a diluent, and micron microspheres. 1 0.2%-0.5%, micron microspheres 2 0.1%-0.3%, antistatic agent 1%-5%, catalyst 1%-3%.

[0007] In one embodiment of the present invention, the substrate layer material is selected from PET, PP or PE.

[0008] In one embodiment of the present invention, the anti-adhesion AB layer is prepared by the following method: various raw materials are mixed, and the obtained mixture is subjected to ultraviolet irradiation reaction to form an anti-adhesion AB layer with a thickness of 1-2 μm.

[0009] In one embodiment of the present invention, the release agent coating is prepared by the following method: mixing the raw materials, and the obtained mixture is roller coated or slit metered extrusion coated, and the coating amount is controlled at 0.6-1.6 g / m 2 It is made by high temperature drying or ultraviolet light curing and then rolling up.

[0010] In one embodiment of the present invention, the oligomer is selected from polyacrylate or polyurethane acrylate oligomers with a functionality of more than 3.

[0011] In one embodiment of the present invention, the diluent monomer is selected from acrylic ester compounds with a functionality of 2 or more.

[0012] In one embodiment of the present invention, the nanospheres 1 and 2 are one or more of nano-alumina, nano-silicon dioxide and nano-zinc oxide; the particle size of the nanospheres 1 is 150-200 nm, and the particle size of the nanospheres 2 is 50-100 nm.

[0013] In one embodiment of the present invention, the photoinitiator is selected from one or more of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylmercaptophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylphenylformyl-diphenylphosphine oxide, xylene ketone and 2-hydroxy-2-methylphenylpropane-1-one.

[0014] In one embodiment of the present invention, the leveling agent is selected from acrylate leveling agent and / or silicone polyether leveling agent.

[0015] In one embodiment of the present invention, the organic silicon main agent is selected from organic silicon polymers containing more than two vinyl groups in the molecule.

[0016] In one embodiment of the present invention, the organosilicon polymer is vinyl-terminated silicone oil, and the structural formula of the vinyl-terminated silicone oil is as follows:

[0017]

[0018] Among them, R 1 is an alkane with 1 to 8 carbon atoms, R 3 It is vinyl, p is 100-2000, q is 0-100, vinyl content is 0.01-0.3%, and viscosity is 1000-100000mPa.s.

[0019] In one embodiment of the present invention, R 1 is methyl, p is 200-2000, the viscosity is 2000-50000 mPa.s, and the molecular weight is 100000-50000; more preferably, the viscosity is 5000-10000 mPa.s, and the molecular weight is 25000-350000.

[0020] In one embodiment of the present invention, the organic silicon polymer is one or more of the LTC759, LTC310 and LTC752 series silicone oils of Dow Chemical.

[0021] In one embodiment of the present invention, the organic solvent is a mixture of a ketone solvent and / or an ester solvent; wherein the volume ratio of the ketone solvent to the ester solvent is (1.5-2.5):1.

[0022] In one embodiment of the present invention, the bridging agent is a hydrogen-containing organosilicon polymer having two or more Si-H bonds in the molecule.

[0023] In one embodiment of the present invention, the hydrogen-containing organosilicon polymer containing more than two Si-H bonds is preferably one or more of DOW Syl-Off7672 and DOW Syl-Off7028.

[0024] In one embodiment of the present invention, the anchoring agent is an organic silicon polymer containing epoxy groups.

[0025] In one embodiment of the present invention, the organic silicon polymer containing epoxy groups is selected from one or more of glycidyltriethoxysilane, anchoring agent DOW Syl-OffSL9106, DOW Syl-OffSL9250 or anchoring agent SL297.

[0026] In one embodiment of the present invention, the diluent is selected from one or more of toluene, xylene, hexane, heptane, acetone, methyl isobutyl ketone, ethyl acetate and butyl acetate.

[0027] In one embodiment of the present invention, the micron microspheres 1 The particle size is 1μm-2μm, the micron microsphere 2 The particle size is 2-5 μm; the micron microsphere 1 and microspheres 2 Independently selected from one or more of alumina, silica, and zinc oxide.

[0028] In one embodiment of the present invention, the antistatic agent is selected from one or more of alkyl sulfonic acid compounds, ethoxylated aliphatic alkylamines, polythiophene compounds, nickel powder, copper powder, silver powder, carbon nanotube particles and quaternary ammonium salts.

[0029] The second object of the present invention is to provide a method for preparing the ultra-light release material with anti-adhesion, which is characterized in that it includes the following steps: coating an anti-adhesion AB layer on one side of the substrate, and then coating a release agent coating on the other side of the substrate to obtain the ultra-light release material with anti-adhesion.

[0030] The present invention provides an anti-adhesion type ultra-light release force release material and a preparation method thereof. The release material not only has the ultra-light release force performance of the release material, but also has a flat release surface and high cleanliness, and can be used for bonding and attaching optical adhesive materials. The back side is treated with an anti-adhesion layer, and the roll-up is smooth and the appearance is neat.

[0031] The above technical solution of the present invention has the following advantages compared with the prior art:

[0032] The technical solution of the present invention has the following advantages over the prior art:

[0033] (1) The release layer of the anti-adhesion release material of the present invention is made of an organic silicon polymer with a certain viscosity and molecular weight structure, which can not only produce a material with ultra-light and stable release force, but also be easy to peel and have stable release force.

[0034] (2) The release layer of the anti-adhesion release material of the present invention adopts an internally added antistatic component, which not only has high temperature resistance and stable release force, but also has an antistatic effect, prevents self-adsorption and adsorption of dust, and ensures the flatness and cleanliness of the surface.

[0035] (3) The anti-adhesion release material release layer of the present invention adds micron-sized microspheres to the silicone, which can prevent the problem of adhesion and adsorption that makes it difficult to peel off after multi-layer stacking. It also has a certain anti-scratch effect to avoid local poor release.

[0036] (4) The anti-adhesion layer treatment on the back of the anti-adhesion release material described in the present invention not only prevents the problem of adhesion and adsorption that makes it difficult to peel off after multiple layers of materials are stacked, but also has a certain anti-scratch effect to avoid local scratch defects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein

[0038] Figure 1 It is a structural diagram of the anti-adhesion ultra-light release material of the present invention. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0040] Example 1

[0041] An anti-adhesion ultra-light release material and a preparation method thereof, specifically comprising the following steps:

[0042] (1) First, an anti-adhesion layer material is applied to one side of the substrate PET film:

[0043] Polyacrylate oligomer (20 parts by mass), Sartomer CN8200NS (polyester acrylate);

[0044] Acrylate monomer (15 parts by mass), Sartomer SR444NS (pentaerythritol triacrylate);

[0045] Nanospheres 1 (150-200nm)(5 parts by mass), nano-alumina;

[0046] Nanospheres 2 (50-100nm) (3 parts by mass), nano-alumina;

[0047] Photoinitiator (3 parts by mass), 1-hydroxycyclohexyl phenyl ketone;

[0048] Leveling agent (2 parts by mass), acrylic leveling agent BYK-354;

[0049] An organic solvent (52 parts by mass) is a mixture of butanone and ethyl acetate, wherein the volume ratio of butanone to ethyl acetate is 2:1;

[0050] After UV irradiation at 80℃*2min, an anti-adhesion layer with a thickness of 1-2μm is formed, which has an anti-adhesion function and a certain anti-scratch effect;

[0051] (2) Then apply the ultra-light release layer material on the other side of the PET film:

[0052] Silicone polymer (30 parts by mass), Dow LTC759;

[0053] Bridging agent (1 part by mass), Dow crosslinker 7672;

[0054] Anchoring agent (1 part by mass), epoxypropyltriethoxysilane;

[0055] Catalyst (1 part by mass), Dow catalyst 4000;

[0056] Diluent (60 parts by mass), toluene;

[0057] Microspheres 1 (1μm-2μm) (0.4 parts by mass), micron-sized silicon dioxide;

[0058] Microspheres 2 (2μm-5μm) (0.2 parts by mass), micron-sized silicon dioxide;

[0059] Antistatic agent (1 part by mass), Wuxi Changhong ASA3010-1SO;

[0060] By roller coating, the coating amount is controlled at 1.2g / m 2 , and is prepared by heat curing at 130℃*2min and then rolling up.

[0061] Example 2

[0062] An anti-adhesion ultra-light release material and a preparation method thereof, specifically comprising the following steps:

[0063] (1) First, apply the anti-adhesion layer material on one side of the substrate PE film:

[0064] Polyurethane acrylate oligomer (25 parts by mass), Sartomer CN8009NS (aliphatic polyurethane acrylate);

[0065] Acrylate monomer (10 parts by mass), SR344 (polyethylene glycol diacrylate);

[0066] Nanospheres 1 (150)(8 parts by mass), nano-silicon dioxide;

[0067] Nanospheres 2 (100nm)(3 parts by mass), nano-silicon dioxide;

[0068] Photoinitiator (5 parts by mass), 1-hydroxycyclohexyl phenyl ketone;

[0069] Leveling agent (2 parts by mass), silicone polyether leveling agent, BYK333;

[0070] An organic solvent (47 parts by mass), wherein the organic solvent is a mixture of acetone and butyl acetate, wherein the volume ratio of acetone to butyl acetate is 2:1;

[0071] After UV irradiation at 80℃*2min, an anti-adhesion layer with a thickness of 1-2μm is formed, which has an anti-adhesion function and a certain anti-scratch effect;

[0072] (2) Then apply the ultra-light release layer material on the other side of the PE film:

[0073] Silicone polymer (35 parts by mass), Dow LTC310;

[0074] Bridging agent (3 parts by mass), Dow 7672;

[0075] Anchoring agent (2 parts by mass), anchoring agent DOW Syl-OffSL9106;

[0076] Catalyst (3 parts by mass), Dow catalyst 4000;

[0077] Diluent (50 parts by mass), xylene;

[0078] Microspheres 1 (1μm-2μm) (0.4 parts by mass), micron-sized silicon dioxide;

[0079] Microspheres 2 (2μm-5μm) (0.2 parts by mass), micron-sized silicon dioxide;

[0080] Antistatic agent (1 part by mass), Shin-Etsu SAS-F16 (solvent-based silicone-added type);

[0081] By roller coating, the coating amount is controlled at 1.2g / m 2 , and is prepared by heat curing at 130℃*2min and then rolling up.

[0082] Example 3

[0083] An anti-adhesion ultra-light release material and a preparation method thereof, specifically comprising the following steps:

[0084] (1) First, apply the anti-adhesion layer material on one side of the PP film of the substrate:

[0085] Urethane acrylate oligomer (25 parts by mass), CN8000NS (aliphatic urethane acrylate);

[0086] Acrylate monomer (10 parts by mass), SR344 (polyethylene glycol diacrylate);

[0087] Nanospheres 1 (150)(8 parts by mass), nano-silicon dioxide;

[0088] Nanospheres 2 (100nm)(3 parts by mass), nano-silicon dioxide;

[0089] Photoinitiator (5 parts by mass), 1-hydroxycyclohexyl phenyl ketone;

[0090] Leveling agent (2 parts by mass), silicone polyether leveling agent BYK333;

[0091] An organic solvent (47 parts by mass) is a mixture of butanone and ethyl acetate, wherein the volume ratio of butanone to ethyl acetate is 2:1;

[0092] After UV irradiation at 80℃*2min, an anti-adhesion layer with a thickness of 1-2μm is formed, which has an anti-adhesion function and a certain anti-scratch effect;

[0093] (2) Then apply the ultra-light release layer material on the other side of the substrate PP film:

[0094] Silicone polymer (35 parts by mass), Dow LTC752;

[0095] Bridging agent (3 parts by mass), Dow 7672;

[0096] Anchoring agent (2 parts by mass), anchoring agent DOW Syl-OffSL9106;

[0097] Catalyst (3 parts by mass), Dow catalyst 4000;

[0098] Diluent (50 parts by mass), hexane;

[0099] Microspheres 1 (1μm-2μm) (0.5 parts by mass), micron-sized silicon dioxide;

[0100] Microspheres 2 (2μm-5μm) (0.1 parts by mass), micron-sized silicon dioxide;

[0101] Antistatic agent (1 part by mass), Shin-Etsu SAS-F16 (solvent-based silicone-added type);

[0102] By roller coating, the coating amount is controlled at 1.0g / m 2 , and is prepared by heat curing at 130℃*2min and then rolling up.

[0103] Example 4

[0104] An anti-adhesion ultra-light release material and a preparation method thereof, specifically comprising the following steps:

[0105] (1) First, an anti-adhesion layer material is applied to one side of the substrate PET film:

[0106] Urethane acrylate oligomer (30 parts by mass), CN8000NS (aliphatic urethane acrylate);

[0107] Acrylate monomer (10 parts by mass), SR444D NS;

[0108] Nanospheres 1 (150-200nm)(8 parts by mass), nano-silicon dioxide;

[0109] Nanospheres 2 (50-100nm) (2 parts by mass), nano zinc oxide;

[0110] Photoinitiator (4 parts by mass), 2-hydroxy-2-methylphenylpropane-1-one;

[0111] Leveling agent (2 parts by mass), silicone polyether leveling agent, BYK310;

[0112] An organic solvent (44 parts by mass) is a mixture of butanone and ethyl acetate, wherein the volume ratio of butanone to ethyl acetate is 2:1;

[0113] After UV irradiation at 80℃*2min, an anti-adhesion layer with a thickness of 1-2μm is formed, which has an anti-adhesion function and a certain anti-scratch effect;

[0114] (2) Then apply the ultra-light release layer material on the other side of the PET film:

[0115] Silicone polymer (40 parts by mass), Dow LTC752;

[0116] Bridging agent (5 parts by mass), Dow 7672;

[0117] Anchoring agent (3 parts by mass), anchoring agent SL297.

[0118] Catalyst (3 parts by mass), Dow catalyst 4000;

[0119] Diluent (40 parts by mass), heptane;

[0120] Microspheres 1 (1μm-2μm) (0.5 parts by mass), micron-sized aluminum oxide;

[0121] Microspheres 2 (2μm-5μm) (0.3 parts by mass), micron-sized silicon dioxide;

[0122] Antistatic agent (1 part by mass), carbon nanotube particles;

[0123] By roller coating, the coating amount is controlled at 1.2g / m 2 , and is prepared by heat curing at 130℃*2min and then rolling up.

[0124] Comparative Example 1

[0125] Apply a release layer only on one side of the PET film:

[0126] Silicone polymer (40 parts by mass), Dow 7458;

[0127] Bridging agent (5 parts by mass), Dow 7672;

[0128] Anchoring agent (3 parts by mass), anchoring agent SL297;

[0129] Catalyst (3 parts by mass), Dow catalyst 4000;

[0130] Diluent (40 parts by mass), heptane;

[0131] By roller coating, the coating amount is controlled at 1.2g / m 2 It is prepared by heating and curing at 150℃*2min and then rolling up.

[0132] Comparative Example 2

[0133] (1) First, a polythiophene solution antistatic layer is coated on the substrate PET film, and then the film is thermally cured at high temperature of 120°C*2min and then rolled up to prepare the film.

[0134] (2) Then apply the ultra-light release layer material on the antistatic layer of the substrate PET film:

[0135] Silicone polymer (40 parts by mass), Dow 7468;

[0136] Bridging agent (5 parts by mass), Dow 7672;

[0137] Anchoring agent (3 parts by mass), anchoring agent SL297;

[0138] Catalyst (3 parts by mass), Dow catalyst 4000;

[0139] Diluent (40 parts by mass), heptane;

[0140] By roller coating, the coating amount is controlled at 1.2g / m 2 It is prepared by curing at 150℃*2min and then rolling up.

[0141] Test Case

[0142] The release force, residual adhesion rate, transmittance, haze, impedance value and other properties of the materials of Examples 1-4 of the present invention and Comparative Examples 1-2 were tested. The specific test methods of the relevant properties are as follows:

[0143] (1) 24h release force (gf / 25mm): Tested in accordance with GB / T 25256-2010 standard;

[0144] (2) 20h aging release force (gf / 25mm): Tested in accordance with GB / T 25256-2010 standard;

[0145] (3) Residual bonding rate (%): Tested in accordance with GB / T 25256-2010 standard;

[0146] (4) Transmittance %: refer to GB / T 2410-2008;

[0147] (5) Haze %: refer to GB / T 2410-2008;

[0148] (6) Impedance value (Ω): refer to GB / T 33375-2016;

[0149] (7) Roughness of release layer (Ra) nm: refer to GB / T 1031-2009;

[0150] (8) AB surface roughness (Ra) nm: refer to GB / T 1031-2009;

[0151] (9) AB surface pencil hardness: refer to GB / T 6739-2006.

[0152] Table 1 shows the relevant parameters finally measured:

[0153] Table 1

[0154]

[0155]

[0156] As can be seen from Table 1, the release layer of the anti-adhesion ultra-light release material prepared by Examples 1-4 of the present invention has an ultra-light release force, a high roughness of the release layer, no adhesion during winding, and excellent release peeling performance. At the same time, the anti-adhesion layer has a certain roughness and pencil hardness, which can prevent the problems of adhesion and scratching during the winding and stacking process of the release film. Comparative Examples 1-2 use a common release layer with a relatively high release force and a relatively low roughness of the release layer. At a certain thickness (0.6 g / m 2 The above) will cause the problem of surface astringency and adhesion. After rolling, it has adsorption and is not easy to peel off. At the same time, there is no anti-adhesion layer on the back. It is easy to cause adhesion and scratches during the stacking process, affecting product quality.

[0157] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. An anti-adhesion ultra-light release material, comprising an anti-adhesion AB layer, a release agent coating, and a substrate layer disposed between the anti-adhesion AB layer and the release agent coating, characterized in that: In mass percentage: The anti-adhesion AB layer comprises 20%-30% oligomer, 5%-15% diluent monomer, 15%-10% nano-microspheres, 23%-5% nano-microspheres, 3%-5% photoinitiator, 1%-2% leveling agent, and 50%-60% organic solvent; The release agent coating comprises 35%-45% of an organic silicon main agent, 1%-5% of a bridging agent, 1%-3% of an anchoring agent, 40%-60% of a diluent, 10.2%-0.5% of micron microspheres, 20.1%-0.3% of micron microspheres, 1%-5% of an antistatic agent, and 1%-3% of a catalyst; The oligomer is selected from one of CN8200NS, CN8009NS, and CN8000NS; The diluent monomer is selected from one of SR444 NS and SR344; The nanospheres 1 and 2 are one or more of nano-alumina, nano-silicon dioxide and nano-zinc oxide; the particle size of the nanospheres 1 is 150-200 nm, and the particle size of the nanospheres 2 is 50-100 nm; The organosilicon main agent is selected from an organosilicon polymer containing more than two vinyl groups in the molecule, and the organosilicon polymer is a vinyl silicone oil, and its structural formula is as follows: ; Wherein, R1 is methyl, R3 is vinyl, p is 200-2000, q is 0-100, vinyl content is 0.01-0.3%, and viscosity is 2000-50000 mpa.s; The particle size of the micron microsphere 1 is 1-2 μm, and the particle size of the micron microsphere 2 is 2-5 μm; the micron microsphere 1 and the micron microsphere 2 are independently selected from one or more of aluminum oxide, silicon dioxide, and zinc oxide; The substrate layer material is selected from PET, PP or PE; The anti-adhesion AB layer is prepared by the following method: mixing various raw materials, and the obtained mixture is subjected to ultraviolet irradiation reaction to form an anti-adhesion AB layer with a thickness of 1-2 μm; The release agent coating is prepared by the following method: mixing the raw materials, and applying the obtained mixture by roller coating or slit metering extrusion coating, and the coating amount is controlled at 0.6-1.6 g / m 2 It is made by high-temperature drying and curing at 130°C for 2 min and then rolling up.

2. The anti-adhesion ultra-light release material according to claim 1, characterized in that: The photoinitiator is selected from one or more of 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-(4-methylmercaptophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylphenylformyl-diphenylphosphine oxide, xylene ketone and 2-hydroxy-2-methylphenylpropane-1-one.

3. The anti-adhesion ultra-light release material according to claim 1, characterized in that: The leveling agent is selected from acrylate leveling agent and / or silicone polyether leveling agent; And / or, the organic solvent is a mixture of a ketone solvent and an ester solvent in a volume ratio of (1.5-2.5):

1.

4. The anti-adhesion ultra-light release material according to claim 1, characterized in that: The viscosity of the silicone polymer is 5000-10000 mpa.s.

5. The anti-adhesion ultra-light release material according to claim 1, characterized in that: The bridging agent is a hydrogen-containing organosilicon polymer containing more than two S1-H bonds in the molecule; and / or, the anchoring agent comprises an organosilicon polymer containing epoxy groups; And / or, the antistatic agent is selected from one or more of alkyl sulfonic acid compounds, ethoxylated aliphatic alkylamines, polythiophene compounds, nickel powder, copper powder, silver powder, carbon nanotube particles and quaternary ammonium salts; And / or, the diluent is selected from one or more of toluene, xylene, hexane, heptane, acetone, methyl isobutyl ketone, ethyl acetate and butyl acetate.

6. The method for preparing the anti-adhesion ultra-light release material according to any one of claims 1 to 5, characterized in that: The following steps are involved: An anti-adhesion AB layer is coated on one side of the substrate, and then a release agent coating is coated on the other side of the substrate to obtain the anti-adhesion ultra-light release material.

Citation Information

Patent Citations

  • Release film with ultralight release force and preparation method thereof

    CN106221595A

  • Anti-adhesion double-faced hardened membrane and preparation method thereof

    CN103755995A

  • Organosilicon release agent with ultra-light release force and preparation method thereof

    CN110819261A

  • Release film for stacked ceramic blank sheets, and preparation method of release film

    CN113683806A